1991
DOI: 10.1111/j.1432-1033.1991.tb15940.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of a secreted acidic protein rich in cysteine (SPARC) in human fibroblasts by transforming growth factor β

Abstract: Transforming growth factor β (TGF‐β) and secreted protein acidic rich cysteine (SPARC) have been associated with the rapid remodeling of connective tissues that occurs in wound healing and developmental processes. To study the temporal and mechanistic aspects of TGF‐β‐regulated extracellular‐protein gene expression in human fibroblasts, confluent cells were pulse labeled for 30 min with [35S]methionine at various times following the single addition of 1.0 ng/ml TGF‐β. After a 4‐h chase period, specific radiola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 59 publications
7
69
1
Order By: Relevance
“…As shown in Figure 2 there was no detectable di erence in the steady-state level of the mRNA between the two extracts. This experiment also indicated that the SPARC message was extremely stable with a half-life of 38+2 h, a value which is in agreement with an independent study conducted in mammalian cells (Wrana et al, 1991). These data led us to pursue the analysis of the repression by v-Jun at the level of an isolated fragment of the SPARC promoter.…”
Section: Transcriptional Repression Of Sparc By V-jun and Modulationsupporting
confidence: 88%
“…As shown in Figure 2 there was no detectable di erence in the steady-state level of the mRNA between the two extracts. This experiment also indicated that the SPARC message was extremely stable with a half-life of 38+2 h, a value which is in agreement with an independent study conducted in mammalian cells (Wrana et al, 1991). These data led us to pursue the analysis of the repression by v-Jun at the level of an isolated fragment of the SPARC promoter.…”
Section: Transcriptional Repression Of Sparc By V-jun and Modulationsupporting
confidence: 88%
“…TGFb is a master regulator of wound-healing and fibrosis by inducing the synthesis of several ECM proteins including collagen and FN1 (Verrecchia and Mauviel, 2007). Ample data demonstrate that TGFb induces SPARC expression (Wrana et al, 1991;Ford et al, 1993;Reed et al, 1994). However, there is also evidence that SPARC regulates the expression and activity of TGFb, suggesting that there is a reciprocal regulatory feedback loop between SPARC and TGFb.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC negatively regulates signaling by various growth factors known to be involved in neural stem cell proliferation and differentiation, including fibroblast growth factor 2 (FGF2) , epidermal growth factor (EGF) (Said et al, 2007a), insulin-like growth factor-1 (IGF-1) (Francki et al, 2003), and transforming growth factor ␤ (TGF␤) (Schiemann et al, 2003;Francki et al, 2004). However, the expression of SPARC is in turn regulated by each of these factors; decreased by FGF2 and EGF, increased by IGF-1, and reciprocally regulated by TGF␤ (Wrana et al, 1991;Chandrasekhar et al, 1994;Delany and Canalis, 1998;Shiba et al, 1998Shiba et al, , 2001. Furthermore, SPARC can positively and negatively modulate growth factor-and adhesion-dependent cell survival signaling (Shi et al, 2004(Shi et al, , 2007Said et al, 2007a), with the potential to maintain neural stem cell equilibrium.…”
Section: Discussionmentioning
confidence: 99%